Algoritma Fisher-Yates sebagai Pengacak Soal pada Game Edukasi: Ruang Geometri - Alma Bryan Fitri Finika; Septi Andryana; Ratih Titi Komalasari (KITA Institute, 2021)
The perception of many students that mathematics is known to be difficult has made the experience negative, so that it has a general impact when adjusting to meeting material calculations. One of the basic materials of mathematics is geometry. This material has provided experiences for Elementary School (SD) children at grade 2 (two) to grade 4 (four). So, one solution is to play with Geometry Space. One of the android-based educational games that provides a media for self-adjustment in understanding material from Geometry. This study designed the Fisher-Yates algorithm in an educational game based on android which is named